Glycerol metabolism and osmoregulation in the salt-tolerant yeast Debaryomyces hansenii. - Adler, L (1985)
A glycerol-nonutilizing mutant of the salt-tolerant yeast Debaryomyces hansenii was isolated. When subjected to salt stress the mutant produced glycerol, and the internal level of glycerol increased linearly in proportion to increases of external salinity as in the wild-type strain. However, at increased salinity the mutant showed a more pronounced decrease of growth rate and growth yield and lost more glycerol to the surrounding medium than did the wild type. Uptake experiments showed glycerol to be accumulated against a strong concentration gradient, and both strains displayed similar kinetic parameters for the uptake of glycerol. An examination of enzyme activities of the glycerol metabolism revealed that the apparent Km of the sn-glycerol 3-phosphate dehydrogenase (EC 1.1.99.5) was increased 330-fold for sn-glycerol 3-phosphate in the mutant. Based on the findings, a scheme for the pathways of glycerol metabolism is suggested.